Cattle house farm / Nur Farah Amira Mustappa Kamal ... [et al.] - Mustappa Kamal, Nur Farah Amira; Mahajid, Marina; Ahmad, Mohamad Eizzul; Mohd Rodi, Muhammad Hafizuddin; Abu Bakar Sedek, Amirah Nabilah Sedek; Ghazali, Fatin Najihah; Mohamad Azman, Siti Nurfatihah (2017)
Entrepreneurship is a process of innovation and new venture creation through four dimensions which includes individuals, organization, environment, and institution. Entrepreneurs are individuals who actively form are lead their own businesses to nurture them for growth and prosperity. In order to form a business, there are quite a number of phases that should be understood and develops by entrepreneurs Cattle House Farm is a business that selling, breeding, and supplies livestock. The business is located at Lot 321 Jalan Haji Hamzah Felda Ayer Hitam, 86100 Kluang, Johor. We choose this business field because we want to develop and improve the agriculture sector in our country. Cattle House Farm will excel due to its attention to detail regarding our users. Through unheralded user's attention, Cattle House Farm will slowly but surely gain market share.